Method and apparatus for reducing power consumption by a disk drive through disk block relocation - COULSON; RICK; GRIMSRUD; KNUT (1998)
An apparatus is programmed with a plurality of programming instructions for generating, if possible, an alternative disk block allocation for a current disk block allocation that will yield reduced overall power consumption for a sequence of disk accesses. In some embodiments, the programming instructions include the logic for tracing the sequence of disk accesses to determine the current disk block allocation, the logic for generating the alternative disk block allocation, if possible, using the trace results, and the logic for effectuating the alternate disk block allocation, if generated. In one particular embodiment, the logic for generating the alternative disk block allocation employs a random search approach, while in another embodiment, the logic for generating the alternative disk block allocation employs a heuristic approach.